2009
DOI: 10.1007/s12272-009-1138-9
|View full text |Cite
|
Sign up to set email alerts
|

Graft preconditioning with low-dose tacrolimus (FK506) and nitric oxide inhibitor aminoguanidine (AGH) reduces ischemia/reperfusion injury after liver transplantation in the rat

Abstract: Ischemia/reperfusion (I/R) injury is a main cause of primary dysfunction or non-function after liver transplantation (LTx). Recent evidence indicates that an increase in nitric oxide (NO) production after LTx is associated with I/R injury. The aim of this study was to demonstrate that low-dose FK506 in combination with aminoguanidine (AGH), which leads to a reduction of NO levels, has a protective effect by reducing I/R associated injury after LTx. Fortyone DA-(RT1av1) rats served as donors and recipients for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 20 publications
1
25
0
3
Order By: Relevance
“…However, large amounts of NO may in turn paradoxically damage liver tissue by forming nitrogen peroxide (40). Husser N. reported that low-dose FK506 in combination with aminoguanidine, which leads to a reduction of NO levels, reduced IRI of the graft after liver transplantation in a rat model (41).…”
Section: Discussionmentioning
confidence: 99%
“…However, large amounts of NO may in turn paradoxically damage liver tissue by forming nitrogen peroxide (40). Husser N. reported that low-dose FK506 in combination with aminoguanidine, which leads to a reduction of NO levels, reduced IRI of the graft after liver transplantation in a rat model (41).…”
Section: Discussionmentioning
confidence: 99%
“…Because pharmaceutical preconditioning of liver grafts is more feasible in the clinical setting than donor preconditioning [32][33][34][35] or post-ischemic treatment [11,36], we studied the addition of a calcineurin inhibitor (tacrolimus; FK506) to the rinse solution. We chose tacrolimus because of recent work demonstrating beneficial effects of this immunosuppressant on reperfusion injury in human liver transplantation [19].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that ROS, either released intracellulary or in the sinusoidal space, might be a target for tacrolimus action [32,40]. Currently, the most important clinical use of tacrolimus is as an immunosuppressant, based on its ability to inactivate T-cells [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental data point to a possible role of calcineurin inhibitor Tacrolimus in IRI attenuation and liver protection during LT (10,11,12). Tacrolimus was shown to be able to inhibit inflammation and immune response in the transplanted liver at the genomic level; the available data on protective function of calcineurin inhibitors in cardiac IRI indicate organ-nonspecific possible mechanism of action (13,14).…”
Section: Introduction Introductionmentioning
confidence: 99%